Quality of Steam-Treated Bayur (Pterospermum javanicum) and Udu (Litsea accedontoides) Wood - Lestari, Dini; Fahrussiam, Fauzan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Steam treatment is one of the thermall modification methods that used to improve the quality of wood, especially wood properties related to the presence of water. This study aims to evaluate quality of 2 types of trade wood in the West Nusa Tenggara region, namely bayur wood (Pterospermum javanicum) and udu (Litsea accedontoides) after steam treatment. Steam treatment was carried out at 126 ◦C for 1 hour using an autoclap device. The parameters tested included the physical properties of wood consisting of density, moisture content, volumetric swelling and Anti Swelling Efficiency (ASE). The mechanical properties of wood tested included Modulus of elasticity (MOE) and Modulus of Rupture (MOR). The results showed that steam treatment did not change the density but reduction in moisture content of bayur and udu wood. Based on the Anti Swelling Efficiency value, steam treatment effectively increased the dimensional stability of udu wood with a value of 88.81%. For mechanical property parameters, steam treatment graphically increased the MOE and MOR values of bayur and udu wood. However, according to SNI 03-3527-1194 there was no increase in the strength class of the two types of wood, and both types of wood were included in strength class III.